JURNAL ASSESSMENT OF INFORMATION TECHNOLOGY GOVERNANCE USING COBIT 2019 FRAMEWORK (CASE STUDY OF NATAR MEDIKA HOSPITAL): PENILAIAN TATA KELOLA TEKNOLOGI INFORMASI MENGGUNAKAN FRAMEWORK COBIT 2019 (STUDI KASUS RS NATAR MEDIKA) - Satria Kusuma, Lutvianus; Wasilah, Wasilah; Purnomo, Hendri (Teknik Komputer Politeknik Negeri Sriwijaya, 2024)
This study evaluates the maturity level of various domains within the COBIT framework in an organization, as well as identifies the gap between current performance and expected performance. The collected data indicates significant differences in maturity levels for domains APO.07, DSS02, DSS.03, DSS.04, DSS.05, and MEA.01, with an average gap of 2.11. Based on these findings, various actions are recommended to improve maturity levels, including increased training and development, adoption of process automation, periodic assessments, improved monitoring and reporting, and more effective risk management. Implementation of these recommendations is expected to reduce the existing gap and enhance overall operational efficiency. Keywords: COBIT, Maturity Level, GAP Analysis, APO.07, DSS02, DSS.03, DSS.04, DSS.05, MEA.01